Single Molecule Study of Hydrogen Bond Interactions Between Single Oligonucleotide and Aerolysin Sensing Interface - Li, Meng-Yin; Wang, Ya-Qian; Lu, Yao; Ying, Yi-Lun; Long, Yi-Tao (Frontiers in Chemistry, 2019)
The aerolysin nanopore displays charming sensing capability for single oligonucleotide discrimination. When reading from the electrochemical signal, the stronger interaction between the aerolysin nanopore and oligonucleotide represent as prolonged duration time, thereby amplifying the hidden but intrinsic signal thus improving the sensitivity. In order to further understand and optimize the performance of the aerolysin nanopore, we focus on the investigation of the hydrogen bond interaction between nanopore and analytes. Taking advantage of site mutagenesis, single residue is replaced. According to whole protein sequence screening, the region near K238 is one of the key sensing regions. Such positively charged amino acid is then mutagenized into cysteine and tyrosine denoted as K238C and K238Y. As (dA)4 traverses the pores, K238C produces dramatically six times longer duration time than the WT aerolysin nanopore at the voltage of +120 mV. However, K238Y shortens the dwell time which suggests the acceleration of the translocation causing poor sensitivity. Referring to our previous findings in K238G and K238F, our results suggest the hydrogen bond does not dominant the dynamic translocation process, but enhance the interaction between pore and analyte confined in such nanopore space. These insights give detailed information for rationally design of the sensing mechanism of the aerolysin nanopore, thereby providing further understanding for the weak interactions between biomolecules and the confined space for nanopore sensing.